'A Long-Legged Fly Upon the Stream': Poetry, Memory and the Unconscious. Issue 4 (1st October 2016) - Bayley, Nicholas
Abstract: In this paper I introduce some concepts from psychoanalysis, a poem, a clinical vignette and a personal anecdote. I am asking what light the knowledge of unconscious processes can throw on the memorisation of poems and therefore what use to the individual can be derived from learning poems by heart. A version of the paper was first given at the Poetry, Memory and Performance conference at Homerton College, University of Cambridge, in March 2015.